The Education Strategy of Anti-bullying Religious Moderation at School - Partono, Partono; Qothrun Nada Illiyuuna; Ashif Az Zafi; Kamil, Tasallia Nima (Tarbawi : Jurnal Ilmu Pendidikan, 2025)
This study explores the role of religious moderation education as a bullying prevention strategy among multireligious school students. The method used in this study is a descriptive qualitative approach, which involves data mining through observation, interviews, and documentation. The research data was analyzed using data reduction, data display, and a conclusion drawn. Triangulation of sources and methods is used for data verification. The study results show that the bullying prevention strategy based on religious moderation education is carried out through, first, integrating religious moderation education into the educational curriculum. Second, the example of teachers in applying religious moderation. Third, students should be involved in religious moderation promotion activities. By emphasizing the importance of respecting differences, rejecting violence, and building solidarity among students, religious moderation is an effective tool to promote harmony in diversity. Overall, the results of this study support the idea that religious moderation can be a very effective strategy in preventing bullying and creating a safer and more comfortable learning atmosphere for all students.